2 Bernard Bush, Laws of the Royal Colony of New Jersey 49 (1980) - (:unkn) unknown (My University, 1704)
"T]hat every Captain within this Province ? make a true and perfect List of all the Men ? between the Age of Sixteen and Fifty years ? Every one of which so listed shall be sufficiently armed with one good sufficient Musquet or Fuzee well fixed, a Sword or Bagonet, a Cartouch-box or Powder-horn, a pound of Powder, and twelve sizeable Bullets."
Keywords: MILITIAS